(untitled) - Sinnen, Oliver (Hoboken, N.J., 2007)
Task scheduling for parallel systems can become a quagmire of heuristics, models, and methods that have been developed over the past decades. The author of this innovative text cuts through the confusion and complexity by presenting a consistent and comprehensive theoretical framework along with realistic parallel system models. Each chapter features exercises that help readers put their new skills into practice. An extensive bibliography leads to additional information for further research. Finally, the use of figures and examples helps readers better visualize and understand complex concepts and processes.
Keywords: Máy tính đa nhiệm (Khoa học máy tính),Lập lịch trình máy tính,Parallel processing (Electronic computers),Computer multitasking (Computer science),Computer scheduling, Xử lý song song (điện tử máy tính)